Proteinase inhibitor-inducing factor activity in tomato leaves resides in oligosaccharides enzymically released from cell walls - Bishop, Paul D. (1981)
The synthesis and accumulation of proteinase inhibitor I in excised tomato leaves can be induced with oligosaccharides obtained by fungal endo-α-1,4-polygalacturonase digestion of a pectic polysaccharide (M(r) 5000-10,000) isolated from tomato leaves. Active oligosaccharides were also released from isolated tomato leaf cell walls by endopolygalacturonases partially purified from tomato plants. It is suggested that oligosaccharides, released from plant cell wall pectic polysaccharides by either endogenous or exogenous endopolygalacturonases at a wound or infection site, may have hormone-like roles in regulating plant defense responses in unwounded tissues many centimeters away from the site of release.